STRATEGIC DIRECTIONS FOR THE FORMATION AND DEVELOPMENT OF DIGITAL SPIRITUAL INTELLIGENCE IN THE INDIVIDUAL (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
The accelerating digitalization of social life has generated unprecedented demands on the psychological and moral capacities of individuals. While constructs such as digital literacy, media literacy, and digital ethics have addressed the competence and behavioral dimensions of digital engagement, they have largely neglected the deeper existential, meaning-making, and transcendent faculties that individuals deploy when navigating digital environments. This theoretical-conceptual article introduces and systematically develops the construct of digital spiritual intelligence (DSI)—defined as the individual’s capacity to apply meaning-oriented, self-transcendent, and ethically reflective cognitive-affective processes to digital experience. Drawing on interdisciplinary synthesis from psychology, education, media psychology, and digital sociology, the article delineates DSI from adjacent constructs including spiritual intelligence, moral intelligence, digital literacy, media literacy, digital ethics, and psychological resilience. The socio-psychological mechanisms underlying the formation of DSI are analyzed through the lenses of self-determination theory, sociocultural theory, and moral identity theory. The article proposes an original multi-level conceptual model—the Integrative Ecological Model of Digital Spiritual Intelligence (IEM-DSI)—that identifies strategic directions for DSI development across personal, familial, educational, social, and institutional levels. The scientific novelty lies in the systematic conceptualization of a hitherto unarticulated construct at the intersection of spirituality and digitality, and in the provision of a theoretically grounded framework for empirical research and educational intervention. The practical significance extends to curriculum development, digital well-being policy, parenting guidance, and institutional design in an increasingly algorithmically mediated society.
Keywords: Digital spiritual intelligence, spiritual intelligence, digital literacy, media psychology, meaning-making, digital ethics, digital well-being, conceptual model, education, digital society.